Prokaryotic community succession and assembly on different types of microplastics in a mariculture cage - Hou, Dandi; Hong, Man; Wang, Kai; Yan, Huizhen; Wang, Yanting; Dong, Pengsheng; Li, Daoji; Liu, Kai; Zhou, Zhiqiang; Zhang, Demin (Environmental pollution (1987), 2021)
Microplastics have emerged as a new anthropogenic substrate that can readily be colonized by microorganisms. Nevertheless, microbial community succession and assembly among different microplastics in nearshore mariculture cages remains poorly understood. Using an in situ incubation experiment, 16S rRNA gene amplicon sequencing, and the neutral model, we investigated the prokaryotic communities attached to polyethylene terephthalate (PET), polyethylene (PE), and polypropylene (PP) in a mariculture cage in Xiangshan Harbor, China. The α-diversities and compositions of microplastic-attached prokaryotic communities were significantly distinct from free-living and small particle-attached communities in the surrounding water but relatively similar to the large particle-attached communities. Although a distinct prokaryotic community was developed on each type of microplastic, the communities on PE and PP more closely resembled each other. Furthermore, the prokaryotic community dissimilarity among all media (microplastics and water fractions) tended to decrease over time. Hydrocarbon-degrading bacteria Alcanivorax preferentially colonized PE, and the genus Vibrio with opportunistically pathogenic members has the potential to colonize PET. Additionally, neutral processes dominated the prokaryotic community assembly on PE and PP, while selection was more responsible for the prokaryotic assembly on PET. The assembly of Planctomycetaceae and Thaumarchaeota Marine Group I taxa on three microplastics were mainly governed by selection and neutral processes, respectively. Our study provides further understanding of microplastic-associated microbial ecology in mariculture environments. [Display omitted] •Prokaryotic communities on three microplastics are distinct in a mariculture cage.•Prokaryotes on microplastics are more similar to the large particle-attached.•Distinct processes govern prokaryotic community assembly on three microplastics. This study provides new insights into the prokaryotic community succession and assembly on different microplastics in a nearshore mariculture cage by a three-month in situ incubation experiment.